The evolution of the gender test score gap through seventh grade: New insights from Australia using unconditional quantile regression and decomposition - Huong Thu Le; Ha Trong Nguyen (IZA Journal of Labor Economics, 2018)
This paper documents the patterns and examines the factors contributing to a gender gap in educational achievements in early seventh grade of schooling using a recent and nationally representative panel of Australian children. Regression results indicate that females excel at non-numeracy subjects at later grades whereas males outperform females in numeracy in all grades, whether at the mean or along the distribution of the test score. Our results also reveal a widening gender test score gap in numeracy as students advance their schooling. Regression and decomposition results also highlight the importance of controlling for pre-school cognitive skills in examining the gender test score gap.
Keywords: I20; J16; 330; Gender; Education; Quantile regression; Decomposition; Australia